Facilitating Flexible, Enquiry-Based Experiential Learning through an Accessible, Three-Dimensional Virtual Learning Environment (3DVLE) : Final Report. - Wood, Denise; Bloustien, Gerry (Australian Learning and Teaching Council (ALTC), 2013)
Final report from a project that demonstrated the pedagogical benefits of the application of three-dimensional virtual world experiences in the undergraduate and graduate curriculum and resulted in the design and development of an accessible, open source 3D virtual learning environment. The team consulted with institutions and networks to ensure stakeholders were involved in the evolution of the 3D virtual learning environment. The development of open source 3D virtual learning environment was guided by pedagogy, accessibility, legal, ethical and intellectual property responsibilities. The project outcomes were disseminated via project website, peer-reviewed journals, conferences, seminars, workshops and public events hosted in 3D virtual spaces.